Role of Koli women in rituals and celebrations - Mumbai Archive Project Team (Jio Institute, 2024)
Koli women play a central role in all the rituals and celebrations. Dressed in traditional attire and jewellery, the women of the household purify the home, perform the puja (prayers of devotional homage) rituals, and prepare the offerings with sincerity and devotion.